2017
DOI: 10.1007/s10921-017-0403-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Crack Surface Orientation in Carbon Fibre Reinforced Polymers by Measuring Electromagnetic Emission

Abstract: Electromagnetic emission (EME) generated by fracture of carbon fibre reinforced polymers (CFRP) is studied. The fracture is induced to cross-ply CFRP by mechanical loading in a three-point bending configuration. An EME acquisition setup operating on the principle of capacitive coupling is used to measure the low frequency (kHz-MHz range) electric field whose generation is attributed to the charge redistribution accompanying the fracture processes. Multiple, differently oriented EME sensors, for the simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The acoustic bond may be formed by a thin layer of a suitable binder. [17] We used plasticine as a binding agent for our measurements. The time of passage through the layer of acoustic bonding material and the through the probe is called dead time.…”
Section: Ultrasonic Pulse Methodsmentioning
confidence: 99%
“…The acoustic bond may be formed by a thin layer of a suitable binder. [17] We used plasticine as a binding agent for our measurements. The time of passage through the layer of acoustic bonding material and the through the probe is called dead time.…”
Section: Ultrasonic Pulse Methodsmentioning
confidence: 99%
“…Photoemissions (in some cases electron emissions) were detected before, during and after fracture. It was observed that photoemissions are prevalent for the weak bonds which fail due to adhesive failure, whereas strong bonds have cohesive failure with less photon emissions [198,199]. Dickinson and co-workers have found that during fracture adhesive bonds and peeling pressure-sensitive adhesives involve large amounts of charge separation and the emission of charged particles, excited neutrals, light and radio waves.…”
Section: Electrical and Electromagnetic Response Of Polymeric And Commentioning
confidence: 99%
“…To understand the crack surface orientation using electromagnetic emissions different source to sensor orientations and distances of antenna have been used. Consequently, a method has been developed in which crack orientation can be known based on the directionality of electromagnetic fields [199]. Langford et al have investigated the photon emissions from fracture of epoxy and have proposed a method to probe fractal surface of the epoxy through the accompanying photoemissions.…”
Section: Electrical and Electromagnetic Response Of Polymeric And Commentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящее время предложено большое количество методов, которые позволяют определять повреждения в бетоне. Среди них метод акустической эмиссии [5,6], электрической и электромагнитной эмиссии [7][8][9], импакт-эхо методы [10,11], ультразвуковые и лазерные методы [12][13][14][15], импедансные методы [16,17] и др. Наряду с этими методами разрабатывается метод оценки повреждения бетона, основанный на характеристиках электрического отклика, возникающего в бетоне в результате импульсного механического воздействия [18][19][20][21].…”
Section: Introductionunclassified